2010
DOI: 10.1016/j.brat.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Overgeneral autobiographical memory as a predictor of the course of depression: A meta-analysis

Abstract: Overgeneral autobiographical memory (OGM) is a robust phenomenon in depression, but the extent to which OGM predicts the course of depression is not well-established. This meta-analysis synthesized data from 15 studies to examine the degree to which OGM 1) correlates with depressive symptoms at follow-up, and 2) predicts depressive symptoms at follow-up over and above initial depressive symptoms. Although the effects are small, specific and categoric/overgeneral memories generated during the Autobiographical M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
275
4
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(318 citation statements)
references
References 51 publications
24
275
4
7
Order By: Relevance
“…Importantly, longitudinal studies and cognitive bias modification (CBM) research (i.e., experimental manipulation of processing biases) have shown that cognitive control deficits (Siegle, Ghinassi, & Thase, 2007;Zetsche & Joormann, 2011), biases in attention (Beevers & Carver, 2003;, interpretation (Blackwell & Holmes, 2010;Holmes, Lang, & Shah, 2009;Rude, Valdez, Odom, & Ebrahimi, 2003;Rude, Wenzlaff, Gibbs, Vane, & Whitney, 2002), and memory processes (Johnson, Joormann, & Gotlib, 2007;Raes, Williams, & Hermans, 2009;Sumner, Griffith, & Mineka, 2010) can predict and contribute to the onset and maintenance of depressive symptoms. Moreover, these distorted cognitive processes can be found in at-risk (Dearing & Gotlib, 2009;Joormann, Talbot, & Gotlib, 2007;Kujawa et al, 2011;Taylor & Ingram, 1999) and remitted (Fritzsche et al, 2010;Gilboa & Gotlib, 1997;Hedlund & Rude, 1995;, 2010 depressed samples.…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, longitudinal studies and cognitive bias modification (CBM) research (i.e., experimental manipulation of processing biases) have shown that cognitive control deficits (Siegle, Ghinassi, & Thase, 2007;Zetsche & Joormann, 2011), biases in attention (Beevers & Carver, 2003;, interpretation (Blackwell & Holmes, 2010;Holmes, Lang, & Shah, 2009;Rude, Valdez, Odom, & Ebrahimi, 2003;Rude, Wenzlaff, Gibbs, Vane, & Whitney, 2002), and memory processes (Johnson, Joormann, & Gotlib, 2007;Raes, Williams, & Hermans, 2009;Sumner, Griffith, & Mineka, 2010) can predict and contribute to the onset and maintenance of depressive symptoms. Moreover, these distorted cognitive processes can be found in at-risk (Dearing & Gotlib, 2009;Joormann, Talbot, & Gotlib, 2007;Kujawa et al, 2011;Taylor & Ingram, 1999) and remitted (Fritzsche et al, 2010;Gilboa & Gotlib, 1997;Hedlund & Rude, 1995;, 2010 depressed samples.…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…Although empirical data from longitudinal studies have found that biases in attention (Beevers & Carver, 2003), interpretation (Rude, Durham-Fowler, Baum, Rooney, & Maestas, 2010;Rude et al, 2003;Rude et al, 2002), memory (Johnson et al, 2007;Sumner et al, 2010) and impairments in cognitive control (Zetsche & Joormann, 2011) can predict depressive symptoms and clinical depression, it is COMBINED COGNITIVE BIAS HYPOTHESIS IN DEPRESSION 25 notable that the obtained effects sizes are often small to moderate. In line with Mathews and MacLeod (2005) we believe that biased cognitive processes can have substantial effects on depression through their mutual interactions and interaction with stressful live events, affecting emotional reactivity to stress that may subsequently lead to depressive symptoms and episodes.…”
Section: Predicting Depressionmentioning
confidence: 99%
“…For example, relative to healthy controls, individuals with depression tend to exhibit superior recall performance for negative emotional information (Everaert et al, 2014;Gaddy & Ingram, 2014). In accordance with Beck's model, findings from longitudinal cohort studies and cognitive bias modification (CBM) studies have demonstrated that this 'negative memory bias' can play a causal role in the onset and maintenance of depressive symptoms (Newby, Lang, Werner-Seidler, Holmes, & Moulds, 2014;Sumner, Griffith, & Mineka, 2010). Memory bias in MDD is thought to be related to altered patterns of functional activity in the amygdala, a limbic structure implicated in the encoding of emotional material (Elliott, Zahn, Deakin, & Anderson, 2011).…”
Section: Introductionmentioning
confidence: 75%
“…Overgeneral memories are common in MDD, in which themselves (e.g., "I always have a bad time at the beach") rather than specific autobiographical episodes (e.g., "this one time I went to the beach and got a sunburn on my knee") [110][111][112]. This overgeneralization of memory appears to be driven by ruminative processes [113], and is a predictor of depression severity [110,114]. It is unclear whether these overgeneral memories are driven by hippocampal failure, leading individuals to operate on a more semantic level, or whether the constant attention towards conceptual elaboration in MDD causes hippocampal atrophy [115].…”
Section: The Hippocampus and Overgeneral Memorymentioning
confidence: 99%